"One and All With a Hip-Hip-Hurrah" : Coverage of the Great War in Wisconsin Newspapers - Hathaway, Steven (My University, 2011)
At the beginning of the 20th century, the world dissolved into chaos in the form of the First World War. Being the first truly modern war, military doctrine and strategy were not able to comprehend the newly acquired advancements in weapons technologies resulting in devastating losses, decimating the male population of Europe. The United States attempted to stay out of the conflict but soon abandoned its isolationist policies to become the "defender of democracies." Alongside the physical combat, the U.S. also had to deal with the war at home. Through the regulation and creation of organizations such as the Associated Press and the Committee on Public Information, most information reaching the American people could be controlled and censored if need be. Through a comparison of newspapers in Wisconsin before and after U.S. declaration of war, an understanding of how these organizations influenced news publications within the state of Wisconsin can be made. As the United States became increasingly active in the war effort, so did its newspapers.
Keywords: World War, 1914-1918--Press coverage--Wisconsin; World War, 1914-1918--Wisconsin--Public opinion; Press and politics--United States--History--20th century.